Temperature-programmed desorption study of molecular oxygen adsorbed on MFI-type zeolites - Kim, MH; Kim, SJ; Hong, SB; Seo, G; Uh, YS (KOREAN INSTITUTE CHEMICAL ENGINEERS, 1998)
The adsorption of molecular oxygen at room temperature on the proton form of MFI zeolites with different Si/Al ratios has been investigated by temperature-programmed desorption (TPD). The internal Si-OH defects (silanol groups) in these zeolites are found to serve as O-2 adsorption sites. The apparent activation energies (17.5-21.8 kcal . mol(-1)) of desorption determined from O-2 TPD measurements reveal that the extent of interactions between the Si-OH defects and the adsorbed O-2 molecules becomes weaker with decreasing Al content in the zeolite.
Keywords: PARAMAGNETIC DEFECT CENTERS; SIEVES; ZSM-5